Determinants of Integrated Management of MSMES on Business Development in the City of Palembang - Utami Putri, Aulia; Khairunnisyah, Tuty; Mirani, Dwi; Mandasari, Lisa (Indonesian Association for Public Administration (IAPA), 2024)
This study examines the determinants of integrated management for MSMEs on business development in Palembang City. Using a quantitative approach and multiple linear regression analysis, the research identifies several factors influencing MSME business development. The analyzed variables include MSME assessment quality, promotion space needs, exhibition facilities, logistics capacity, digital literacy, development of online business aggregators, and customized coaching programs tailored to the potential and challenges of MSMEs. The results reveal that customized business program development has the most significant impact on business development, followed by the implementation of coaching programs. In contrast, exhibition facilities show a negative effect on business growth. With an R-squared value of 82.3%, the model exhibits strong predictive capabilities. Managerial implications highlight the importance of an integrated approach to MSME development, emphasizing digital technology, literacy, and collaboration to achieve sustainability. The study suggests that the government and other stakeholders focus on developing adaptive programs and sustained coaching to support the growth of MSMEs in Palembang.